Drying–rewetting cycles and γ-irradiation effects on enzyme activities of distinct layers from a Quercus ilex L. litter - Alarcón-Gutiérrez, Enrique; Floch, Carine; Ziarelli, Fabio; Augur, Christopher; Criquet, Stéven (Soil Biology and Biochemistry, 2010)
In a Mediterranean climate, water stress is one of the principal constraints on proper forest ecosystem functioning. Drought influences rates of organic matter degradation by affecting microbial growth and enzyme activities. The objectives of this study were: (i) to evaluate the effect of repeated dryingerewetting cycles on cellulase, alkaline phosphatase and fluorescein diacetate (FDA) hydrolase activities of three distinct Quercus ilex L. litter layers, and (ii) to investigate the effect of these cycles on γ-irradiated litters in order to distinguish the abiotic influence on the fluctuations observed. Results, for all three layers, showed high correlations between litter water content and enzyme activities. Under mesocosm conditions, and using non-sterilized litter samples, cellulase, alkaline phosphatase, and FDA activities significantly decreased or increased during drying or rewetting cycles respectively. Significant differences were also found when evaluating the effect of litter depth on enzyme activities, the intermediate depth (OLv layer) generally being the most active. For γ-sterilized samples, FDA activity still fluctuated with dryingerewetting cycles. Assays showed that pre-humidification of γ-irradiated litter increased FDA activity two-fold in the first 30 min. All these results have shown that, following dryingerewetting cycles, some of the fluctuations occur independently of microbial growth, suggesting abiotic interactions, such as desorption, in combination with both solvatation status and conformational changes of enzymes.
Keywords: abiotic fluctuations; Drying-rewetting; Enzyme activities; Moisture; γ-Irradiation

Measurement and characterization of cellulase activity in sclerophyllous forest litter. - Criquet, Stéven (Journal of microbiological methods, 2002)
Cellulases are enzymatic proteins which hydrolyze cellulose polymers to smaller oligosaccharides, cellobiose and glucose. They consist in three major types of enzymes: endoglucanases (EC 3.2.1.4), cellobiohydrolases (EC 3.2.1.91) and beta-glucosidases (EC 3.2.1.21) which play an essential role in carbon turnover of forest ecosystem. The aim of this study was firstly to determine the parameters (i.e. buffer type, pH, temperature, quantity of litter, incubation time and reagent type) which affect the measurement of cellulase activity in a sclerophyllous forest litter, and secondly to compare two methods for measuring cellulase activity: a direct method and an extraction method. In the direct method, the litter was directly incubated with a buffered solution containing the enzyme substrate, whereas in the extraction method, the cellulases were firstly extracted before measuring their activity. The results were compared with other studies about soil cellulase activity, and it appeared that several parameters (buffer type, pH, temperature and sample quantity) which influence the measurement of cellulase activity differ according to whether a soil or a litter is considered. Concerning the procedure used for the measurement of cellulase activity, results showed that the activity values were higher when using an extraction procedure than when using a direct procedure. The extraction procedure, combined with a concentration stage of the extract, also allowed electrophoretic analysis (PAGE) of the cellulases extracted from the litter. The electrophoretic pattern revealed two cellulase isoenzymes which may be related to the occurrence of two pH-activity peaks of these enzymes when citrate buffer was used for the measurement of cellulase activity in the litter.
The following values have no corresponding Zotero field: accession-num: 11997167
Keywords: Buffers; Cellulase; Cellulase: analysis; Cellulase: isolation & purification; Cellulose; Cellulose: metabolism; Endoglucanase; Extraction; Hydrogen-Ion Concentration; Isoenzyme; Isoenzymes; Isoenzymes: analysis; litter; Plant Leaves; Plant Leaves: enzymology; Quercus; Quercus: enzymology; Temperature; Trees

Measurement and characterization of cellulase activity in sclerophyllous forest litter. (Journal of microbiological methods, 2002)
Cellulases are enzymatic proteins which hydrolyze cellulose polymers to smaller oligosaccharides, cellobiose and glucose. They consist in three major types of enzymes: endoglucanases (EC 3.2.1.4), cellobiohydrolases (EC 3.2.1.91) and beta-glucosidases (EC 3.2.1.21) which play an essential role in carbon turnover of forest ecosystem. The aim of this study was firstly to determine the parameters (i.e. buffer type, pH, temperature, quantity of litter, incubation time and reagent type) which affect the measurement of cellulase activity in a sclerophyllous forest litter, and secondly to compare two methods for measuring cellulase activity: a direct method and an extraction method. In the direct method, the litter was directly incubated with a buffered solution containing the enzyme substrate, whereas in the extraction method, the cellulases were firstly extracted before measuring their activity. The results were compared with other studies about soil cellulase activity, and it appeared that several parameters (buffer type, pH, temperature and sample quantity) which influence the measurement of cellulase activity differ according to whether a soil or a litter is considered. Concerning the procedure used for the measurement of cellulase activity, results showed that the activity values were higher when using an extraction procedure than when using a direct procedure. The extraction procedure, combined with a concentration stage of the extract, also allowed electrophoretic analysis (PAGE) of the cellulases extracted from the litter. The electrophoretic pattern revealed two cellulase isoenzymes which may be related to the occurrence of two pH-activity peaks of these enzymes when citrate buffer was used for the measurement of cellulase activity in the litter.